2023
DOI: 10.3390/biomedicines11020399
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanomaterials for Drug Delivery

Abstract: In recent years, nanomedicine has provided several high-performance tools for overcoming biomedical challenges, resulting in numerous patents [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…76 A broad spectrum of cytokine profiles was observed, and it was demonstrated that the plasma level of E2 was twice as high as the normal level. 76 Wang et al investigated the neurological characteristic of methylhistamine (MH), which could target the recurrent process that is activated during an injury, to identify a potential therapeutic intervention for the treatment of PNI. To produce a drug with a sustained release, a complex was produced of the pharmaceutical with Dx sulfate by using an interaction that was supported by metal ions.…”
Section: Agarose (Ag) Based Polysaccharide Drug Delivery Systems For ...mentioning
confidence: 99%
See 4 more Smart Citations
“…76 A broad spectrum of cytokine profiles was observed, and it was demonstrated that the plasma level of E2 was twice as high as the normal level. 76 Wang et al investigated the neurological characteristic of methylhistamine (MH), which could target the recurrent process that is activated during an injury, to identify a potential therapeutic intervention for the treatment of PNI. To produce a drug with a sustained release, a complex was produced of the pharmaceutical with Dx sulfate by using an interaction that was supported by metal ions.…”
Section: Agarose (Ag) Based Polysaccharide Drug Delivery Systems For ...mentioning
confidence: 99%
“…For neuroprotection in SCI, Cox et al 78 made PLGA Nps which is full of estrogen (E2). 76 A rat model of spinal cord injury that ranged from mild to severe was utilized to assess the effectiveness of the scaffold. To create the framework, the E2-loaded PLGA Nps that were produced via the nanoprecipitation process were combined with an AG hydrogel.…”
Section: Agarose (Ag) Based Polysaccharide Drug Delivery Systems For ...mentioning
confidence: 99%
See 3 more Smart Citations